Effect of acid catalysts on hydrothermal carbonization of Malaysian oil palm residues (leaves, fronds, and shells) for hydrochar production - Ameen, M. (Springer Science and Business Media Deutschland GmbH, 2022)
Malaysian oil palm industry produces a significant amount of oil palm residue as solid wastes. These solid wastes are comprised of oil palm residue which contains the stem, fronds from the farms, empty fruit bunch (EFB), mesocarp fibre (MF), and palm kernel shell (PKS) from the oil palmâprocessing factories. These residues are not successfully reused for other purposes, and the current dumping methods can possibly trigger unfavourable effects to the environment. As oil palm residues are a readily available waste biomass, it has a high potential to be converted into valuable energy-derived products. Hydrothermal carbonization (HTC), which is a thermochemical process, is a method used to treat biomass to produce hydrochar under hot-compressed water. Oil palm residues (palm leaves, palm fronds, and palm shell) were used as the feedstock for producing carbonaceous hydrochar. The key objective of this study is to examine the effect of the reaction temperature, residence time, and acid catalysts on the HTC process. HTC of oil palm residues was optimized at different operating temperatures from 140 to 300 Â°C and different reaction times between 30 and 240 minutes with a biomass-to-water ratio of 1:10 wt. Acid catalysts such as citric acid and ascorbic acid were used for the HTC process. The hydrochar produced is further characterized using heating value and elemental and Fourier transform infrared (FTIR) analysis. The yield of hydrochar reduces with the rise of temperature and time but it increases in the presence of acid catalysts. The carbon content of hydrochar is observed to be between 44.36 and 49.50. The FTIR analysis showed that a high intensity at 1423 cmâ1 indicates a high content of lignin and cellulose in the hydrochar. A considerable decrease in the H/C and O/C atomic ratio shows that the dehydration and decarboxylation take place during the HTC process. Figure not available: see fulltext. Â© 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH, DE part of Springer Nature.